Labor Market I. Data from the German Federal Employment Services - Stefan Bender; Joachim Möller (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2009)
This contribution shows the increasing supply on German micro data over the last years for labor market research. We focus on the research data centre movement, the development of new anonymisation techniques for establishment data, the new challenges of the social code II and the fundamental change to evaluate labor market programmes actively with administrative data. Although a lot of ongoing developments like combining different data sets are happening, we make three recommendations for future developments in this area: (1) Demand to have an influence an the data production. (2) The need to combine data sets (especially across national borders) (3) Importance to establish an international infrastructure for data access.
Keywords: 330; labor market; data access; administrative data; linked employer employee data; research data center; social code II; evaluation